(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
In this essay I develop a critique of Will Kymlicka’s model of multicultural justice, with the purpose of laying down the foundations for a critical multiculturalism. The argument is ordered in the following way. In the first section I analyse Kymlicka’s theory of special rights and identify the central liberal value to which they respond: individual autonomy. In the second section I examine the luck egalitarian foundations of Kymlicka’s theory of special rights. In the third section, I elaborate a general critique to liberal multicultural justice, developing an argument to politicize the claims of indigenous peoples to access to their culture. Basically I argue that the just treatment of indigenous minorities requires recognizing their political self-determination.